Collaborative Governance: Contradictions of the National Apprenticeship Program in Karawang Regency-Indonesia - Safaranita Nur Effendi Yeni Effendi; Luki Oka Prastio; Selvi Centia (Social Impact Journal, 2022)
This study aims to examine the achievements of employment policies through the National Apprenticeship Program in Karawang-Indonesia which is actually marked by the conflict between the government, the private sectors, and the community. This study uses a qualitative approach, with primary data obtained through direct observation and in-depth interviews, while secondary data is obtained from relevant research literature and documents. The results of the study show that the achievement of collaboration in the implementation of employment in Karawang Regency in the form of the National Apprenticeship Program is unattractive for the job seekers, ineffective in reducing the high unemployment rate, and is far from feasible in industrial relations with workers. In addition to the magnitude of the contradiction in the program's objectives, it is manifested in many divorces and terms of interest, it is prone to violations that in practice lead to labor exploitation or neo-slavery. Keywords : Collaborative Governance, National Apprenticeship, Karawang Regency.